Keywords Co-occurrence Analysis of Research on Sustainable Enterprise and Sustainable Organisation - Lis, Andrzej (Journal of Corporate Responsibility and Leadership, 2019)
Purpose: The aim of the paper is to identify and explore leading thematic areas within the research field related to a sustainable enterprise/organisation. The following research questions are asked to achieve the aim of the study: (1) What are the leading areas/topics of scientific inquiry in the research field? (2) What is the research status in the leading research areas/topics? (3) What are the most up-to-date (emerging) topics in the field? Design/methodology/approach: Analysis of keywords co-occurrence is the bibliometric method used to map the research field. The methodology of systematic literature review is applied in order to conduct the analysis of research status in the identified leading thematic areas within the research field. Findings: The study identifies and discusses seven streams of research associated with the concept of a sustainable enterprise i.e. (1) sustainable development and sustainable enterprise idea, (2) sustainability, (3) strategic management and functional areas management, (4) human and organisational context, (5) sustainable manufacturing, (6) industrial context and (7) environmental management. Moreover, emerging, ‘hot’ topics attracting a growing attention of the research community in recent years are enumerated, which include such issues as: (1) the concept of the sustainable, smart and sensing enterprise, (2) sustainable enterprise resource planning and allocation, (3) building competitive advantage in a sustainable enterprise, (4) managing sales in a sustainable enterprise, (5) managing sustainable supply chains, and (6) developing sustainable enterprise excellence. Research and practical limitations/implications: Mapping of the research field and identifying emerging topics provides guidelines for further studies, which can be considered as valuable contribution to the theory and research development. However, due to the theoretical character of the study its practical implications are rather limited. Originality/value: As a bibliometric study, the paper generates the added value mainly from the point of view of the theory development. Its originality derives from a very limited number of studies which use the methodology of keywords analysis to map the research field and identify leading topics within it. Paper type: review paper.